A kind of carbon-based negative electrode material for sodium ion battery and its preparation process

By using biomass lignin to prepare nitrogen-containing porous carbon ball materials as the negative electrode material of sodium ion battery, the problems of poor circulation performance and low capacity of sodium ion battery negative electrode material are solved, and high specific capacity and good cycle stability are achieved.

CN116081619BActive Publication Date: 2025-04-04ZHUHAI KECHUANG SODIUM ELECTRIC TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310096431.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-10
Publication Date
2025-04-04
Estimated Expiration
2043-02-10

AI Technical Summary

Technical Problem

The negative electrode material of sodium ion battery has poor circulation performance and low capacity, which limits the practical application of sodium ion battery.

Method used

Using biomass lignin as the carbon source, cross-linking by cross-linking by reacting Schiff base with dihydrazine and lignin aldehyde groups to a high specific surface area to prepare a nitrogen-containing porous carbon sphere material as the negative electrode material for sodium ion batteries.

Benefits of technology

The conductivity and specific capacity of porous carbon sphere materials are improved, the transmission of electrons and sodium ions is promoted, and the cyclic stability and specific capacity of the negative electrode materials are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116081619B_ABST
    Figure CN116081619B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sodium ion batteries, and discloses a carbon-based negative electrode material for sodium ion batteries and a preparation process thereof. The aldehyde-based lignin of biomass is used as a carbon precursor, and bishydrazine and the aldehyde group of lignin are reacted by Schiff base to perform cross-linking, and porous bishydrazine cross-linked lignin microspheres are prepared by a reverse suspension method. Finally, high-temperature carbonization is performed to obtain a nitrogen-containing porous carbon sphere material with a high specific surface area as the negative electrode material of the sodium ion battery. Nitrogen doping to form structures such as pyridine nitrogen and graphite nitrogen improves the conductivity and specific capacity of the porous carbon sphere material. The porous structure of the carbon sphere promotes the transmission of electrons and the embedding and de-embedding process of sodium ions in the electrode material, thereby improving the cycle stability performance of the negative electrode material, and obtaining a sodium ion battery with superior cycle performance and high specific capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a carbon-based negative electrode material for a sodium ion battery and a preparation process thereof. Background Art

[0002] Compared with lithium-ion batteries, sodium-ion batteries have the advantages of lower cost and abundant sodium source reserves. However, sodium-ion batteries have defects such as low specific capacity and low energy density, which limit their practical application. The negative electrode material of sodium-ion batteries has a great influence on the capacity and energy density of the battery. The development of high-performance sodium-ion battery negative electrode materials is a research hotspot.

[0003] The negative electrode materials of sodium ion batteries mainly include carbon-based materials, alloy materials, metal oxide materials, etc. Among them, carbon-based materials have good cycle performance, a wide range of carbon precursor sources, and a variety of preparation processes. They are a very promising negative electrode material, such as patent 202111476574.2 "CN114361450A A nitrogen-doped porous carbon nanofiber sodium ion battery negative electrode material and its preparation method", which discloses that nitrogen-doped porous carbon fiber materials have stable physical and chemical properties, a wide range of raw material sources and low cost, good electrochemical performance, high safety, and as electrodes, have high rate performance and good cycle stability. The present invention uses biomass lignin as a carbon source to obtain nitrogen-doped porous carbon balls as negative electrode materials for sodium ion batteries. Summary of the invention

[0004] 1. Technical issues to be solved

[0005] The present invention provides a carbon-based negative electrode material for a sodium ion battery, which solves the problems of poor cycle performance and low capacity of the negative electrode material for a sodium ion battery.

[0006] (II) Technical solution

[0007] A carbon-based negative electrode material for a sodium ion battery, the negative electrode material consists of a nitrogen-containing porous carbon ball material with a mass ratio of 75-85%, a binder of 8-12%, a conductive agent of 7-13%, and an aluminum foil or copper foil current collector. The nitrogen-containing porous carbon ball material is prepared by cross-linking bishydrazine and aldehyde lignin to form microspheres, which are then carbonized at high temperature.

[0008] The preparation process of carbon-based negative electrode materials for sodium ion batteries includes the following steps:

[0009] S1: Add aldehyde lignin to distilled water, add dihydrazine after ultrasonic dispersion and stir to dissolve as the water phase, then add liquid paraffin and surfactant Span 80 as the oil phase, stir to react, add the water phase to ethanol for precipitation, filter the solvent, wash with ethanol, and obtain dihydrazine cross-linked lignin microspheres.

[0010] S2: The dihydrazine cross-linked lignin microspheres and potassium hydroxide are mixed evenly, put into a tubular furnace, and carbonized at 700-850° C. in a nitrogen atmosphere for 2-3 hours, and the carbonized product is washed with distilled water until it is neutral to obtain a nitrogen-containing porous carbon sphere material.

[0011] Preferably, the amount of bishydrazine in S1 is 20-50% of the weight of lignin.

[0012] Preferably, the volume ratio of distilled water to liquid paraffin in S1 is 2-4:1.

[0013] Preferably, the reaction temperature in S1 is 55-70° C. and the reaction time is 2-4 h.

[0014] Preferably, the preparation process of the aldehyde lignin in S1 comprises the following steps:

[0015] S3: adding lignin to a sodium hydroxide aqueous solution with a concentration of 6-10%, then dropping an aqueous solution of trimethylamine, heating to 60-80°C, then dropping chloroform, stirring and reflux reaction for 6-12h, dropping hydrochloric acid solution after the reaction for precipitation, filtering, and washing with distilled water to obtain aldehyde lignin.

[0016] (III) Beneficial technical effects

[0017] Using the aldehyde lignin of biomass as a carbon precursor, bishydrazine and the aldehyde group of lignin undergo Schiff base reaction for cross-linking, and porous bishydrazine cross-linked lignin microspheres are prepared by a reverse suspension method. Finally, high-temperature carbonization is performed to obtain nitrogen-containing porous carbon sphere materials with high specific surface area as negative electrode materials for sodium ion batteries. Nitrogen doping to form pyridine nitrogen, graphite nitrogen and other structures improves the conductivity and specific capacity of the porous carbon sphere materials. The porous structure of the carbon spheres promotes the transmission of electrons and the deintercalation and insertion process of sodium ions in the electrode material, thereby improving the cycle stability of the negative electrode material, and obtaining a sodium ion battery with superior cycle performance and high specific capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is the cell charge and discharge voltage specific capacity curve DETAILED DESCRIPTION

[0019] Example 1

[0020] (1) 3 g of lignin was added to 100 mL of a 10% sodium hydroxide aqueous solution, and then an aqueous solution containing 1.2 g of trimethylamine was added dropwise, the temperature was raised to 70°C, and then 40 mL of chloroform was added dropwise, stirred and refluxed for reaction for 12 h. After the reaction, a hydrochloric acid solution was added dropwise for precipitation, filtered, and washed with distilled water to obtain aldehyde lignin.

[0021] (2) 2 g of formaldehyde lignin was added to 20 mL of distilled water, and after ultrasonic dispersion, 0.4-1 g of bishydrazine was added and stirred to dissolve as the water phase, and then 5 mL of liquid paraffin and 0.6 g of surfactant Span 80 were added as the oil phase. The temperature was raised to 70 ° C and stirred for reaction for 3 h. After the reaction, the water phase was added to ethanol for precipitation, the solvent was filtered, and the ethanol was washed to obtain bishydrazine cross-linked lignin microspheres.

[0022] (3) 2 g of bis(hydrazine)-crosslinked lignin microspheres and 4 g of potassium hydroxide were mixed evenly, placed in a tubular furnace, and carbonized at 800° C. in a nitrogen atmosphere for 2 h. The carbonized product was washed with distilled water until it was neutral to obtain a nitrogen-containing porous carbon sphere material.

[0023] (4) 80% by weight of nitrogen-containing porous carbon ball material, 10% of binder polyvinylidene fluoride, and 10% of conductive agent carbon black are added to N-methylpyrrolidone, and after dispersion, the slurry is coated on the surface of the copper foil current collector, and after drying, the carbon-based negative electrode material 1 is obtained.

[0024] Example 2

[0025] (1) 3 g of lignin was added to 150 mL of a 10% sodium hydroxide aqueous solution, and then an aqueous solution containing 1.5 g of trimethylamine was added dropwise, the temperature was raised to 70° C., and then 50 mL of chloroform was added dropwise, stirred and refluxed for 6-12 h. After the reaction, hydrochloric acid solution was added dropwise for precipitation, filtered, and washed with distilled water to obtain aldehyde lignin.

[0026] (2) 2 g of formaldehyde lignin was added to 10 mL of distilled water, and after ultrasonic dispersion, 0.6 g of bishydrazine was added and stirred to dissolve as the water phase, and then 5 mL of liquid paraffin and 0.7 g of surfactant Span 80 were added as the oil phase. The temperature was raised to 70 ° C and stirred for reaction for 3 h. After the reaction, the water phase was added to ethanol for precipitation, the solvent was filtered, and the ethanol was washed to obtain bishydrazine cross-linked lignin microspheres.

[0027] (3) 2 g of dihydrazine cross-linked lignin microspheres and 4 g of potassium hydroxide were mixed evenly, placed in a tubular furnace, and carbonized at 650° C. in a nitrogen atmosphere for 3 h. The carbonized product was washed with distilled water until it was neutral to obtain a nitrogen-containing porous carbon sphere material.

[0028] (4) 75% by weight of nitrogen-containing porous carbon ball material, 12% of binder polyvinylidene fluoride, and 13% of conductive agent carbon black are added to N-methylpyrrolidone, and after dispersion, the slurry is coated on the surface of the copper foil current collector, and after drying, the carbon-based negative electrode material 2 is obtained.

[0029] Example 3

[0030] (1) 3 g of lignin was added to 200 mL of an 8% sodium hydroxide aqueous solution, and then an aqueous solution containing 1.6 g of trimethylamine was added dropwise, the temperature was raised to 80° C., and then 50 mL of chloroform was added dropwise, stirred and refluxed for reaction for 12 h. After the reaction, hydrochloric acid solution was added dropwise for precipitation, filtered, and washed with distilled water to obtain aldehyde lignin.

[0031] (2) 2 g of formaldehyde lignin was added to 15 mL of distilled water, and after ultrasonic dispersion, 1 g of bishydrazine was added and stirred to dissolve as the water phase, and then 5 mL of liquid paraffin and 0.8 g of surfactant Span 80 were added as the oil phase. The temperature was raised to 60 ° C and stirred for reaction for 3 h. After the reaction, the water phase was added to ethanol for precipitation, the solvent was filtered, and the ethanol was washed to obtain bishydrazine cross-linked lignin microspheres.

[0032] (3) 2 g of bis(hydrazine)-crosslinked lignin microspheres and 4 g of potassium hydroxide were mixed evenly, placed in a tubular furnace, and carbonized at 750° C. for 2 h in a nitrogen atmosphere. The carbonized product was washed with distilled water until it was neutral to obtain a nitrogen-containing porous carbon sphere material.

[0033] (4) 80% by weight of nitrogen-containing porous carbon ball material, 10% of binder polyvinylidene fluoride, and 10% of conductive agent carbon black are added to N-methylpyrrolidone, and after dispersion, the slurry is coated on the surface of the copper foil current collector, and after drying, the carbon-based negative electrode material 3 is obtained.

[0034] Example 4

[0035] (1) 3 g of lignin was added to 150 mL of a 10% sodium hydroxide aqueous solution, and then an aqueous solution containing 1.2 g of trimethylamine was added dropwise, the temperature was raised to 70°C, and then 60 mL of chloroform was added dropwise, stirred and refluxed for 12 h. After the reaction, hydrochloric acid solution was added dropwise for precipitation, filtered, and washed with distilled water to obtain aldehyde lignin.

[0036] (2) 2 g of formaldehyde lignin was added to 20 mL of distilled water, and after ultrasonic dispersion, 0.4-1 g of bishydrazine was added and stirred to dissolve as the water phase, and then 5 mL of liquid paraffin and 0.7 g of surfactant Span 80 were added as the oil phase. The temperature was raised to 55 ° C and stirred for reaction for 3 h. After the reaction, the water phase was added to ethanol for precipitation, the solvent was filtered, and the ethanol was washed to obtain bishydrazine cross-linked lignin microspheres.

[0037] (3) 2 g of bis(hydrazine)-crosslinked lignin microspheres and 4 g of potassium hydroxide were mixed evenly, placed in a tubular furnace, and carbonized at 800° C. in a nitrogen atmosphere for 2 h. The carbonized product was washed with distilled water until it was neutral to obtain a nitrogen-containing porous carbon sphere material.

[0038] (4) 85% by weight of nitrogen-containing porous carbon ball material, 8% of binder polyvinylidene fluoride, and 7% of conductive agent carbon black are added to N-methylpyrrolidone, and after dispersion, the slurry is coated on the surface of the copper foil current collector, and after drying, the carbon-based negative electrode material 4 is obtained.

[0039] Example 5

[0040] (1) 3 g of lignin was added to 200 mL of a 6-10% sodium hydroxide aqueous solution, and then an aqueous solution containing 1.8 g of trimethylamine was added dropwise, the temperature was raised to 60° C., and then 50 mL of chloroform was added dropwise, stirred and refluxed for reaction for 6-12 h. After the reaction, a hydrochloric acid solution was added dropwise for precipitation, filtered, and washed with distilled water to obtain aldehyde lignin.

[0041] (2) 2 g of formaldehyde lignin was added to 20 mL of distilled water, and after ultrasonic dispersion, 0.4 g of bishydrazine was added and stirred to dissolve as the water phase, and then 5 mL of liquid paraffin and 0.6-1 g of surfactant Span 80 were added as the oil phase. The temperature was raised to 70 ° C and stirred for reaction for 2 h. After the reaction, the water phase was added to ethanol for precipitation, the solvent was filtered, and the ethanol was washed to obtain bishydrazine cross-linked lignin microspheres.

[0042] (3) 2 g of dihydrazine cross-linked lignin microspheres and 4 g of potassium hydroxide were mixed evenly, placed in a tubular furnace, and carbonized at 700° C. in a nitrogen atmosphere for 3 h. The carbonized product was washed with distilled water until it was neutral to obtain a nitrogen-containing porous carbon sphere material.

[0043] (4) 80% by weight of nitrogen-containing porous carbon ball material, 10% of binder polyvinylidene fluoride, and 10% of conductive agent carbon black are added to N-methylpyrrolidone, and after dispersion, the slurry is coated on the surface of the copper foil current collector, and after drying, the carbon-based negative electrode material 5 is obtained.

[0044] The sodium sheet was used as the positive electrode, and the carbon-based negative electrode material prepared in Examples 1-5 was wound with a PE separator coated with 12+4 alumina ceramic, assembled, and baked. The liquid was injected at a rate of 12 g / piece, the concentration of sodium hexafluorophosphate was 1 mol / L, and the solvent was an electrolyte of ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC) = 1:1:1. After injection, the electrolyte was subjected to formation, aging, and capacity separation processes to prepare 32700 battery cells. The battery cells prepared in Examples 1-5 are A1-A5, respectively.

Claims

1. A carbon-based negative electrode material for a sodium ion battery, the negative electrode material being composed of a nitrogen-containing porous carbon ball material with a mass ratio of 75-85%, a binder of 8-12%, a conductive agent of 7-13%, and an aluminum foil or copper foil current collector, characterized in that: The nitrogen-containing porous carbon sphere material is prepared by cross-linking bishydrazine and aldehyde-based lignin to form microspheres, and then carbonizing at high temperature; The preparation process comprises the following steps: S1: Add aldehyde lignin to distilled water, add dihydrazine after ultrasonic dispersion and stir to dissolve as the water phase, then add liquid paraffin and surfactant Span 80 as the oil phase, stir to react, add the water phase to ethanol for precipitation, filter the solvent, wash with ethanol, and obtain dihydrazine cross-linked lignin microspheres. S2: The bishydrazine cross-linked lignin microspheres and potassium hydroxide are mixed evenly, placed in a tube furnace, and carbonized at 700-850° C. in a nitrogen atmosphere for 2-3 hours, and the carbonized product is washed with distilled water until it is neutral to obtain a nitrogen-containing porous carbon sphere material; The preparation process of the aldehyde lignin in S1 comprises the following steps: S3: adding lignin to a sodium hydroxide aqueous solution with a concentration of 6-10%, then dropping an aqueous solution of trimethylamine, heating to 60-80°C, then dropping chloroform, stirring and reflux reaction for 6-12h, dropping hydrochloric acid solution after the reaction for precipitation, filtering, and washing with distilled water to obtain aldehyde lignin.

2. The carbon-based negative electrode material for sodium ion batteries according to claim 1, characterized in that: The amount of bishydrazine in S1 is 20-50% of the weight of lignin.

3. The carbon-based negative electrode material for sodium ion batteries according to claim 1, characterized in that: The volume ratio of distilled water to liquid paraffin in S1 is 2-4:

1.

4. The carbon-based negative electrode material for sodium ion batteries according to claim 1, characterized in that: The reaction temperature in S1 is 55-70°C and the reaction time is 2-4h.

Citation Information

Patent Citations

  • Nitrogen-doped porous carbon nanofiber sodium ion battery negative electrode material and preparation method thereof

    CN114361450A